2011
DOI: 10.1038/hdy.2011.122
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to a bacterial parasite in the crustacean Daphnia magna shows Mendelian segregation with dominance

Abstract: The influence of host and parasite genetic background on infection outcome is a topic of great interest because of its pertinence to theoretical issues in evolutionary biology. In the present study, we use a classical genetics approach to examine the mode of inheritance of infection outcome in the crustacean Daphnia magna when exposed to the bacterial parasite Pasteuria ramosa. In contrast to previous studies in this system, we use a clone of P. ramosa, not field isolates, which allows for a more definitive in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 43 publications
6
42
3
Order By: Relevance
“…Furthermore, the data show that variation for resistance is mostly determined by clone identity, as replicates within clones are highly consistent with each other, suggesting little non-genetic variation (Figure 1a). These results were not surprising: a previous study using genetic crosses had shown that D. magna's resistance against P. ramosa is likely based on a locus with Mendelian inheritance, without evidence for non-genetic effects (Luijckx et al, 2012). However, this previous study, using material from Finnish populations exclusively, revealed a second locus strongly linked to the first, coding for resistance against a different P. ramosa genotype (Luijckx et al, 2013).…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…Furthermore, the data show that variation for resistance is mostly determined by clone identity, as replicates within clones are highly consistent with each other, suggesting little non-genetic variation (Figure 1a). These results were not surprising: a previous study using genetic crosses had shown that D. magna's resistance against P. ramosa is likely based on a locus with Mendelian inheritance, without evidence for non-genetic effects (Luijckx et al, 2012). However, this previous study, using material from Finnish populations exclusively, revealed a second locus strongly linked to the first, coding for resistance against a different P. ramosa genotype (Luijckx et al, 2013).…”
Section: Discussioncontrasting
confidence: 48%
“…Assuming that resistance is dominant and coded by a single locus with two alleles, the proportion of susceptible clones would be expected to be 25%, which is not significantly different from 20.6% (χ 2 = 1.986, P = 0.16, n = 195). This single locus Mendelian segregation was also seen for Pasteuria resistance in a cross between two Finnish D. magna clones (Luijckx et al, 2012). The QTL analysis of these binary (0/1) infection data (clones being treated as susceptible or resistant) revealed a single major QTL that explains 50.04% of the total variation ( Figure 1c and Table 1).…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Numerous field studies identified the presence of comprehensive heritable variation in resistance-infectivity patterns for plant and animal populations and their respective pathogens, suggesting that coevolution acts to maintain genetic diversity [3,11,[52][53][54][55]. However, already the first studies, which attempted to explain such variation by cycling dynamics, encountered the problem of stability.…”
Section: Implications For Maintenance Of Genetic Diversitymentioning
confidence: 99%
“…As resting eggs are very tolerant of chemical treatment (Vizoso et al, 2005;Luijckx et al, 2012), we used household bleach (sodium hypochlorite) instead of antibiotics to remove the bacteria from the egg surfaces. We also used autoclaved algae instead of axenic live algae as alternative food to the Daphnia.…”
Section: Daphnia From Resting Eggsmentioning
confidence: 99%